2003
DOI: 10.1128/jcm.41.4.1788-1790.2003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of False Positives during Testing for Antibodies to Hepatitis C Virus among Volunteer Blood Donors in India

Abstract: The hepatitis C virus antibody statuses of only 11 (21.5%) of 51 initially reactive samples from volunteer blood donors could be confirmed by using additional screening and confirmatory assays; 23 (45%) were negative by all subsequent assays. Seventeen samples (33.3%) gave variable results in the different assays. The core and NS5 antigens were most immunogenic. An algorithm for serological screening of volunteer blood donors in blood banks of developing countries is suggested.The high rate of chronicity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
11
1
1
Order By: Relevance
“…An independent study conducted in the same locality at about the same time showed an HCV antibody prevalence of 3.3% in women of childbearing age [Combe et al, 2001]. However, the enzyme immunoassay used in the study has been associated with false-positive results [Njouom et al, 2003;Raghuraman et al, 2003]. A more recent report using molecular assays showed the prevalence of HCV infection in Côte d'Ivoire to be 1% [Rouet et al, 2004], which is three times lower than the rate reported here.…”
Section: Discussioncontrasting
confidence: 63%
“…An independent study conducted in the same locality at about the same time showed an HCV antibody prevalence of 3.3% in women of childbearing age [Combe et al, 2001]. However, the enzyme immunoassay used in the study has been associated with false-positive results [Njouom et al, 2003;Raghuraman et al, 2003]. A more recent report using molecular assays showed the prevalence of HCV infection in Côte d'Ivoire to be 1% [Rouet et al, 2004], which is three times lower than the rate reported here.…”
Section: Discussioncontrasting
confidence: 63%
“…It suggests that: (i) an initial screening with a single G3 EIA is preferable in our setting since the combined use of two first-line EIAs did not allow to identify HCV seroconversion, and all discordant specimens had negative or indeterminate results on supplemental testing; (ii) the choice of a firstline G3 EIA must take into account both its analytical performance (including the definition of a cutoff breakpoint below which a positive result can be generally considered as non-specific) and its cost. Indeed, as indicated in package inserts from manufacturers and as described previously [Tess et al, 2000;Ampofo et al, 2002;Ayele et al, 2002;Njouom et al, 2003], anti-HCV positive specimens with low absorbance values are frequent in tropical areas, possibly reflecting the multiplicity of intercurrent infections occurring in these areas that lead to hyperglobulinemia contributing to false positive results with anti-HCV EIAs [Trepo et al, 1993;Raghuraman et al, 2003]. In our experience, a high frequency of non-specific positive samples was also observed with low positive S/C ratios ( 4) during the primary screening, especially with the Murex assay.…”
Section: Discussionmentioning
confidence: 89%
“…This phenomenon further reinforces the importance for investigating further before beginning treatment. False positives with ELISA cannot be completely ruled out in Africa where studies have shown that Africans produce antibodies that react non-specifically with ELISAs and have even prompted the development of newer generations of ELISA [8][9][10]. Figure 3.…”
Section: Discussionmentioning
confidence: 99%